Challenges on management of heart failure in Indonesia: a general practitioner’s perspective (Medical Journal of Indonesia, 2014)
Heart failure has become a public health problem with increasing incidence and prevalence. Many patients first came to the primary care and managed by general practitioner. Accurate diagnosis is essential to provide good management of heart failure. However, symptoms and signs alone are often neither sufficient nor specific to confirm the diagnosis. Some studies show that heart failure patients are still incorrectly diagnosed and inadequately treated, despite the availability of current guidelines. Inadequacy of facilities is the main obstacle in diagnosing and managing heart failure, especially in developing countries like Indonesia. The medications recommended for treating heart failure are still under-prescribed. This review discuss about the challenges of diagnosis and management of heart failure in primary care. Keywords: heart failure, general practice, primary care